An updated review of alien species on the coasts of Turkey - CINAR, M.E.; BILECENOGLU, M.; OZTURK Β.; KATAGAN Τ.; YOKES Μ.Β.; AYSEL, V.; DAGLI, E.; ACIK, S.; OZCAN, T.; ERDOGAN, H. (Mediterranean Marine Science, 2011)
This 2010 review of alien species along the coasts of Turkey represents a total of 400 alien species belonging to 14 systematic groups. The present paper also reports the first findings ofVanderhorstia mertensi in the Aegean Sea (Gökova Bay), Chama adspersa in the Sea of Marmara andMya arenaria in the Aegean Sea. A total of 124 new alien species was determined within the last 5 years. Mollusca had the highest number of species (105 species), followed by Polychaeta (75 species), Crustacea (64 species) and Pisces (58 species). The highest number of alien species (330 species) were encountered on the Levantine coast of Turkey, followed by the Aegean Sea (165 species), Sea of Marmara (69 species) and Black Sea (20 species). The Suez Canal (66% of the total number of alien species) is the main vector for species introductions to the coasts of Turkey, followed by the ship-mediated transport (30%). The majority of species (306 species, 76% of total number of species) have become established in the area, while 59 species are classified as casual (15%), 23 species as questionable (6%) and 13 species as cryptogenic (3%). One new alien species was introduced to the coasts of Turkey every 4 weeks between 1991 and 2010. The majority of aliens were found on soft substratum (198 species) in shallow waters (0-10 m) (319 species). Some species such asCaulerpa racemosa, Amphistegina lobifera, Amphisorus hemprichii, Rhopilema nomadica, Mnemiopsis leidyi, Hydroides spp., Ficopomatus enigmaticus, Charybdis longicollis, Rapana venosa, Asterias rubens, Siganus spp. and Lagocephalus sceleratus show high invasive characters, and have great impacts both on the prevailing ecosystems and humans.